T1 Energetic deficiency and adenosine receptor signalling in cardiac fibrosis. (21st March 2018) - Stockenhuber, A; Ghafari, S; Kelly, M; Steeples, V; Czibik, G; Tyler, D; Støttrup, N; Yavari, A; Watkins, H; Ashrafian, H
Abstract : Myocardial fibrosis (MF) contributes to the pathogenesis of cardiac hypertrophy secondary to energetic perturbation. Recent evidence suggests an increase of purine signalling upon energetic deficiency and specifically a role of adenosine signalling in tissue fibrosis. The specific objective of this study was to delineate adenosine A2A receptors in the development of MF. In vitro, isolated cardiac fibroblasts demonstrated a significant increase in collagen production upon A2A receptor stimulation. This was inhibited by addition of a specific A2A receptor inhibitor. In vivo, models of cardiac hypertrophy including the transverse aortic constriction (TAC) model and cardiac actin E99K transgenic mice (E99K mice) were investigated as murine models for MF. In E99K mice a reduced phosphocreatine/ATP ratio was demonstrated using magnetic resonance spectroscopy. Interstitial adenosine levels measured by microdialysis correlated with collagen content, showing energy deficiency and a correlation with MF. Crossbreeding of E99K and Adenosine A2A receptor knock out (A2A KO) mice resulted in a significant reduction of MF in E99K heterozygous A2A KO animals. A2A KO mice undergoing TAC demonstrated significantly less fibrosis formation compared to wild type mice upon measurement of myocardial collagen and on histology. This was associated with a significant rescue of cardiac function. Finally, pharmacologic adenosine A2A receptor inhibition using the antagonist ZM241385 demonstrated a partial rescue effect on MF in both TAC and E99K animals. This data indicates that signalling of energy deficiency via adenosine A2A receptors play a crucial role in the formation of MF and that this pathway is susceptible to pharmacologic modulation.